2017
DOI: 10.5152/turkthoracj.2017.16022
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Silent Brain Metastasis Before Prophylactic Cranial Irradiation in Small Cell Lung Cancer

Abstract: OBJECTIVES:Prophylactic cranial irradiation (PCI) decreases incidence of brain metastasis and improves survival in patients with limited disease-small cell lung cancer (LD-SCLC) who achieved complete response (CR) after treatment. There is no satisfactory evidence about the necessity of new brain imaging for asymptomatic metastasis immediately prior to PCI. The present study aimed to evaluate the frequency of brain metastasis in SCLC patients without neurological symptoms who are candidates for PCI. MATERIAL A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Although previous studies have explored the risk factors of BM in SCLC, there are some deficiencies [20,[32][33][34][35][36][37][38][39][40][41]. First, brain MRI was not used as a standard measure and was only performed with symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although previous studies have explored the risk factors of BM in SCLC, there are some deficiencies [20,[32][33][34][35][36][37][38][39][40][41]. First, brain MRI was not used as a standard measure and was only performed with symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…First, brain MRI was not used as a standard measure and was only performed with symptoms. For this reason, some patients with brain metastasis were included in these studies, resulting in the inability to accurately evaluate the related factors of brain metastasis [32,[35][36][37][38][39][40]. Second, some studies have taken PCI as a factor related to brain metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…The study also found a reduction in BM with a HR 0.45 (95% CI: 0.38-0.55) in favour of PCI though there was significant heterogeneity in brain imaging following chemo-radiation (7). Restaging magnetic resonance imaging (MRI) brain following completion of chemo-radiation should be considered given that interval BM occur in 20-32% of patients (8,9). However, even following a negative restaging brain MRI, BM subsequently occur in 37-41% of patients without PCI (10,11).…”
Section: Prophylactic Cranial Irradiation (Pci) In Ls-sclcmentioning
confidence: 94%
“…Prior to initiating PCI after completion of CRT, a brain MRI should be performed for re-evaluation. In patients with chest CR, MRI performed after CRT shows an incidence of BM ranging from 20%-32%[ 137 , 138 ].…”
Section: Pci In Limited and Es Diseasementioning
confidence: 99%